Bacterial symbiont diversity in Arctic seep Oligobrachia siboglinids - Sen, Arunima; Tanguy, Gwenn; Galand, Pierre, E; Andersen, Ann, C; Hourdez, Stéphane (Animal Microbiome, 2023)
International audience Abstract Background High latitude seeps are dominated by Oligobrachia siboglinid worms. Since these worms are often the sole chemosymbiotrophic taxon present (they host chemosynthetic bacteria within the trophosome organ in their trunk region), a key question in the study of high latitude seep ecology has been whether they harbor methanotrophic symbionts. This debate has manifested due to the mismatch between stable carbon isotope signatures of the worms (lower than -50‰ and usually indicative of methanotrophic symbioses) and the lack of molecular or microscopic evidence for methanotrophic symbionts. Two hypotheses have circulated to explain this paradox: (1) the uptake of sediment carbon compounds with depleted δC 13 values from the seep environment, and (2) a small, but significant and difficult to detect population of methanotrophic symbionts. We conducted 16S rRNA amplicon sequencing of the V3-V4 regions on two species of northern seep Oligobrachia ( Oligobrachia webbi and Oligobrachia sp. CPL-clade), from four different high latitude sites, to investigate the latter hypothesis. We also visually checked the worms’ symbiotic bacteria within the symbiont-hosting organ, the trophosome, through transmission electron microscopy. Results The vast majority of the obtained reads corresponded to sulfide-oxidizers and only a very small proportion of the reads pertained to methane-oxidizers, which suggests a lack of methanotrophic symbionts. A number of sulfur oxidizing bacterial strains were recovered from the different worms, however, host individuals tended to possess a single strain, or sometimes two closely-related strains. However, strains did not correspond specifically with either of the two Oligobrachia species we investigated. Water depth could play a role in determining local sediment bacterial communities that were opportunistically taken up by the worms. Bacteria were abundant in non-trophosome (and thereby symbiont-free) tissue and are likely epibiotic or tube bacterial ...